23.83% efficient mono‐PERC incorporating advanced hydrogenation. (24th January 2020) - Chen, Ran; Tong, Hongbo; Zhu, Haitao; Ding, Chao; Li, Hua; Chen, Daniel; Hallam, Brett; Chong, Chee Mun; Wenham, Stuart; Ciesla, Alison
Abstract: LONGi Solar Energy Technology Co. Ltd. has achieved 23.83% for a commercial p‐type Cz PERC cell. From a batch of over 40 000 cells, the average line efficiency achieved was 22.5%. R&D studies investigating hydrogenation and degradation show the importance of hydrogenation processes for efficiency improvements and controlling the hydrogen to prevent light‐induced degradation. Such degradation is shown to appear very differently under different illumination and temperature conditions. This degradation impacts V OC, I SC, and especially fill factor. Current injection and thermal anneal can be used to recover the degradation, but the recovery may not be stable. Reducing the hydrogen content within the cell is shown to minimise degradation without sacrificing performance, provided that enough hydrogen is retained to passivate boron‐oxygen defects. Abstract : LONGi achieved 23.83% for commercial p‐type Czochralski PERC cells. Investigations show the importance of hydrogenation processes for efficiency improvements and solutions to prevent light‐induced degradation which appears differently under different illumination and temperature conditions. Current injection and thermal anneal can be used to recover the degradation, but the recovery may not be stable. Reducing the hydrogen content within the cell is shown to minimise degradation without sacrificing performance, provided that enough hydrogen is retained to passivate boron‐oxygen defects.